PENGEMBANGAN SISTEM INFORMASI MANAJEMEN RUMAH MAKAN (SIMRAHMAN) STUDI KASUS RUMAH MAKAN MEMORY GARDEN PURWOKERTO - Fany Aditya Rahman; Suhartono Suhartono; Eko Adi Sarwoko (Journal of Informatics and Technology, 2012)
Economic competition is very tight now, especially for restaurant. The manager as restaurant policy control always has to get accurate informations and up to date. The Memory Garden Restaurant was one of restaurant that was located in Purwokerto. Previously, every operational activity and restaurant report still applied manual system by using paper. That system could be difficult for employees to give services for the customers, especially when there are many customers come. The manager got difficulty to investigate stack of data at the paper in large number for getting informations. It could be taken benefit by employees to do dishonest. To solve these problems, Memory Garden Restaurant needs management information system. Incremental model has been taken as process model to build the new system. This restaurant management information system, or called SIMRAHMAN, has been developed using programming language of Visual Basic.NET and DBMS of MySql. SIMRAHMAN can support working for all employees and help managing restaurant operational and result informations completely and accurately, so can give the best service to customers.